Estimating New Zealand's Output Gap Using a Small Macro Model - Kam Leong Szeto (New Zealand Government, The Treasury, 2013)
The Treasury has been testing the assumptions on the potential growth rate of the New Zealand economy. In this paper, we estimate a small macro model using Bayesian techniques, which allows us to assess the level of uncertainty of the estimates of the output gap. The model is based on the work of Benes et al. (2010) with some modifications reflecting New Zealand economic conditions. Although this new technique does not reduce the uncertainty in measures of potential output as indicated by large confidence bands for the estimates, it provides us a useful tool with an economic framework for measuring potential output.
Keywords: C32; C53; E31; E32; 330; Potential output; Potential growth rate; Output gap; Unemployment; NAIRU; Inflation and Capacity